Metode Pendidikan Islam Menurut Ibnu Qayyim Al-Jauziyah - Uswatul Hasanah, Eti Shobariyah (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2017)
Ibn Qayyim Al-Jauziyah is a Muslim figure whose thoughts are very broad and very deep and pay great attention to education. But in reality, Ibn Qayyim was not said to be a scholar in the field of education, he was better known as an expert in Fiqh. This is because Ibn Qayyim wrote about Jurisprudence in the Hambali school. In this study, the author uses the method of library research, which is a way to find out the thoughts of a character, namely Ibn Qoyyim Al-Jauziyah, by examining the fruits of his work in order to obtain data about his thoughts in full and be supported by other sources of relevant relevance. with the thought of Ibn Qoyyim Al-Jauziyah. The conclusions of this research are: Islamic education method is a way to understand, explore, and develop Islamic teachings so that they continue to develop in accordance with the times and human activity to improve their personality by fostering personal spiritual potentials (thought, taste, intention, and conscience). The method according to Ibn Qayyim is a memorization method, lecture method, exemplary method, habituation method, story or advice method, story or story method, giving a method of Hadiya or punishment. The objectives of Ibn Qayyim's perspective of Islamic education are Ahdaf Jismiyah (faith), Ahdaf Akhlakiyah (morals), Ahdaf Fikriyah (reason) and Ahdaf Maslakiyah (skills). The Teacher's Ethics according to Ibn Qayyim Al-Jauziyyah is a teacher must have ethics that must be fulfilled for himself, morals of Murabbi (Teacher), ethics of Murabbi (Teacher) towards students, and ethics of Mutarabbi (students) towards his teacher, Ibnu Qayyim also appealed to a teacher must be able to understand the psychological theory of students. Because Islamic education is an important factor in fostering students who in the future can personally change towards a better and implemented based on Islamic teachings.